Effects of environmental management accounting on environmental performance of manufacturing companies in Malaysia - Munusamy, Tamilselvi (2016)
Environmental issues are attracting increase attention in Malaysia with tremendous increase in waste generation; cost of production and waste treatment is getting expensive. Environmental data shows that 80% of the wasted was generated by the manufacturing industry. It also indicates that future natural resources are being squandered as waste due to less exposure in the environmental management accounting which end up to unproductivity, overproduction, increase in total delivery cost or inefficiency in manufacturing plant. Purpose - This research exploits the quantitative research methodology to understand the relationship between contingent factors which are uncertainty environment, organizational size, environmental strategy, regulatory pressure and top management commitment that influence the environmental management accounting and environmental performance among manufacturing companies in Klang Valley, Selangor. Design/methodology/approach – Survey conducted on manufacturing companies that are located in Klang Valley, from the Federal Malaysian Manufacturer (FMM) database. 600 questionnaires were sent out to manufacturing companies, with most of the question using Likert scale. Smart PLS 3 the second generation multivariate was used to simulate the model. Findings – Total usable sample was 114 manufacturing companies, which suggested that uncertainty in the environment, regulator pressure and top management commitment significantly impact environmental management accounting. With environmental management accounting, the companies able to improve environmental performances for example input and output target yield of raw material being define, in daily routine reporting and meeting it to be discuss too. If the yield of that day was below the target this indicating that more wastage had occur. At that point the management team could immediately detect and address the issue promptly to avoid further waste from occurring. Originality/value of paper – This study presents empirical knowledge towards the understanding of the driving factors of environmental management accounting practices in Malaysia. It considers that environmental issues are closely associated with business sustainability agendas; policy makers should recognize the need to instill efficiency, productivity, wastage and lower total delivery cost in all manufacturing practices.